Morphological Evaluation of Taro ( Colocasia esculenta Linn.) Genotypes Collected from Manipur State of India and their Yield Performance - Swarnalata Devi, Kh; James Singh, K; Bijaya Devi, A K; Mandal, Joydip; Birkumar Singh, H (JOURNAL OF ROOT CROPS, 2017)
A total of nine traditional genotypes or cultivars of taro ( Colocasia esculenta (L.) Schott), locally called Hao-paan , Ingkhol-paan , Lam-paan , Mukhi-paan angangba , Mukhi-paan angouba , Paan-angangba , Paan-gong , Singda-paan and Yerum-paan have been collected and identified from Manipur. These plants are widely consumed by ethnic people of Manipur in various forms of traditional cuisines. The cultivars namely Mukhi-paan angangba , Ingkhol-paan and Paan-angangba are generally accepted as the tasty among the nine. The botanical characteristics and agronomic data of the nine cultivars were studied for morphological traits such as corm shape, size and other yield parameters using RBD with three replicates. The yield of corm and cormel was highest in Mukhi-paan angouba (604 g plant -1 ) while least in Lam-paan (205 g plant -1 ). Considering the taste and yield the four genotypes namely, Mukhi-paan angangba , Mukhi-paan angouba , Paan-angangba and Ingkhol-paan are preferred for commercial cultivation.